Save Your Vision Week 1988 - Poster Contest Follow-up - Optometrists, Canadian Association of (Canadian Journal of Optometry, 2026)
On behalf of CAO and Canada's 2,700 optometrists, we thank Wayne and the entire Oilers' organization for helping us promote "Life Is Worth Seeing!'' so successfully this year. And we'll leave the final word on the subject to 11-year old Donny Newberry. whose prize, we were advised, included his first-ever flight and first trip outside the province of Ontario.